PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA KAZOR PANGKAS RAMBUT WAGIR MALANG - Rozak, Abdur; Aditama, Roni Angger (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2025)
This research aims to determine the extent to which service quality and price influence customer satisfaction at Kazor Pangkas Rambut Wagir Malang. The hypotheses tested are 1) service quality is thought to partially influence customer satisfaction at Kazor Pangkas Rambur Wagir Malang; 2) price is thought to partially influence customer satisfaction at Kazor Barbershop Wagir Malang; 3) service quality and price are thought to simultaneously influence customer satisfaction at Kazor Pangkas Rambut Wagir Malang. This research uses quantitative methods. The data sources used are primary and secondary. Meanwhile, data analysis uses multiple linear regression. The results of the research concluded: There is an influence of Service Quality on Customer Satisfaction at Kazor Pangkas Rambur Wagir Malang. Second, there is an influence of price on customer satisfaction at Kazor Pangkas Rambur Wagir Malang. Third, there is an influence of service quality and price together on customer satisfaction at Kazor Pangkas Rambur Wagir Malang. All three show that Service Quality and Price contribute to Customer Satisfaction at Kazor Pangkas Rambur Wagir Malang.